2023
DOI: 10.1002/psp.2706
|View full text |Cite
|
Sign up to set email alerts
|

Life events, social conditions and residential mobility among older adults

Brian Joseph Gillespie,
Tineke Fokkema

Abstract: This study explores whether and how social conditions—ties to kin and friends as well as loneliness—are related to older adults' residential mobility, in general, and in combination with a late‐life event, specifically. Drawing on panel data from the US Health and Retirement Study (N = 9107), logistic regression models examine whether older adult moves are triggered by life events (retirement, widowhood and health deterioration) and loneliness, and discouraged by the presence of nearby social ties (family and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Some who move for proximity to family might do so to use their family network to escape unemployment (Gillespie et al, 2021) or find better jobs (as suggested by the findings of Clark and Maas [2015]). Others might do so to find refuge in an adverse situation (Spring et al, 2023) or in response to loneliness (Gillespie & Fokkema, 2023). Yet others might move in response to their own or their family members' care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Some who move for proximity to family might do so to use their family network to escape unemployment (Gillespie et al, 2021) or find better jobs (as suggested by the findings of Clark and Maas [2015]). Others might do so to find refuge in an adverse situation (Spring et al, 2023) or in response to loneliness (Gillespie & Fokkema, 2023). Yet others might move in response to their own or their family members' care needs.…”
Section: Introductionmentioning
confidence: 99%